Massive star formation in the Tarantula Nebula - Nayak, Omnarayani; Green, Alex; Hirschauer, Alec S.; Indebetouw, Rémy; Meixner, Margaret; Wong, Tony; Chevance, Mélanie; Marchi, Guido De; Lebouteiller, Vianney; Lee, Min-Young; Looney, Leslie W.; Madden, Suzanne C.; et al. (The astrophysical journal, 2023)
In this work, we present 299 candidate young stellar objects (YSOs) in 30 Doradus discovered using Spitzer and Herschel point-source catalogs, 276 of which are new. We study the parental giant molecular clouds in which these YSO candidates form using recently published Atacama Large Millimeter/submillimeter Array (ALMA) Cycle 7 observations of 12CO and 13CO. The threshold for star formation in 30 Doradus inferred by the LTE-based mass surface density is 178 M ⊙ pc−2, 40% higher than the threshold for star formation in the Milky Way. This increase in star formation threshold in comparison to the Milky Way and increase in line width seen in clumps 11 pc away in comparison to clumps 45 pc away from the R136 super star cluster could be due to injected turbulent energy, increase in interstellar medium pressure, and/or local magnetic field strength. Of the 299 YSO candidates in this work, 62% are not associated with 12CO molecular gas. This large fraction can be explained by the fact that 75%-97% of the H2 gas is not traced by CO. We fit a Kroupa initial mass function to the YSO candidates and find that the total integrated stellar mass is 18,000 M ⊙ and that the region has a star formation rate (SFR) of 0.18 M ⊙ yr−1. The initial mass function determined here applies to the four 150″ × 150″ (37.5 pc × 37.5 pc) subfields and one 150″ × 75″ (37.5 pc × 18.8 pc) subfield observed with ALMA. The SFR in 30 Doradus has increased in the past few million years.
Gesehen am 24.04.2023